Beyond Administration: Reconstructing Marriage Registration as a Preventive Legal Protection for Women and Children in Indonesia - Sutriyono Sutriyono; A. Halil Thahir; Ahmad Sarwini (Al-Qalam Institute, 2026)
This study examines marriage registration as a legal protection instrument for women and children through the perspectives of Maqāṣid al-Sharīʿah and Sadd al-Dharīʿah. This study employs normative legal research using statutory, conceptual, and Islamic legal-philosophical approaches. Legal materials were collected through legal document and literature studies involving legislation, court decisions, Islamic legal sources, scholarly literature, and relevant previous studies. The materials were analyzed using normative-qualitative analysis by interpreting and synthesizing legal norms based on Maqāṣid al-Sharīʿah and Sadd al-Dharīʿah. The findings show that marriage registration is not merely an administrative requirement but a preventive legal protection instrument that provides legal certainty and facilitates the fulfillment of women’s and children’s rights. From the Maqāṣid al-Sharīʿah perspective, registration supports the protection of lineage, property, life, and dignity, while Sadd al-Dharīʿah positions registration as a mechanism for preventing potential harms arising from unregistered marriages. The study contributes a normative reconstruction of marriage registration as a maqāṣid-based legal protection instrument, providing a conceptual basis for strengthening marriage registration policies and protecting women and children.